Peningkatan Hasil Belajar IPAS Menggunakan Model Problem Based Learning Di Kelas IV SD Negeri 088/II Sungai Mengkuang - Ruviah, Saniatun; Megawati, Megawati; Pitra, Dedek Helida (Master of Pedagogy and Elementary School Learning, 2025)
Based on preliminary observations, the inadequate quality of the learning process and learning results in the Science, Environment, and Social Studies (IPAS) topic inspired the fourth-grade students at SD Negeri 088/II Sungai Mengkuang to participate in this classroom action research project.  This study's goal was to use the Problem Based Learning (PBL) methodology to enhance IPAS learning outcomes.  “Classroom Action Research (CAR), which was conducted in two cycles, was the research methodology employed.  The phases of planning, action implementation, observation, and reflection made up each cycle.  32 fourth-graders served as the study's subjects.  Test instruments, instructor observation sheets, and student observation sheets were among the methods used to collect data”.  Both quantitative and qualitative methods of data analysis were used. The findings demonstrated that the PBL model's implementation enhanced IPAS's learning outcomes and process.  An average score of 90.5% in Cycle II compared to 71.5% in Cycle I demonstrated the teacher's progress in their teaching methodology.  The average percentage of learning activities completed by students rose with each cycle, from 37.5% in Cycle I to 68.5% in Cycle II.  Furthermore, in Cycle II, the IPAS learning outcomes rose from 53% in Cycle I to 78%.  Thus, it can be said that fourth-grade students at SD Negeri 088/II Sungai Mengkuang benefit from the application of the Problem Based Learning approach in terms of their IPAS learning outcomes